Pig the slob - Blabey, Aaron (Blabey, Aaron. Pig the pug (Series), 2020)
When Pig the pug's lifestyle of lounging on the couch and binging snacks and television comes to a crashing end, his daschund friend Trevor introduces the joys of jogging and eating nutritious meals.